Chinese temples and shrines: An exploratory study on its functions / Kong Lai Mei - Kong, Lai Mei (1984)
This academic exercise is a modest attempt at exploring the functions and significance of Chinese Temples and Shrines to the Chinese Community. Field study was carried out in Petaling Jaya for a duration of 3 months, from April 1984 - July 1984, where a total of 18 temples and shrines were visited. In Chapter One, the aims, methodology and problems of search is discussed. Chapter Two, is a review of materials on Confucianism, Taoism and Buddhism, touching on the syncretic nature of Chinese Religion. A discussion on the functions of Temples and Shrines is also included here. Chapter Three is a write out on the historical background, characteristics, organization and finances of Temples and Shrines. In Chapter Four, we are introduced to the various types of festivals that are celebrated. Since these festivals are usually held to celebrate the birthday of deities, a brief description on the background of some deities will be included. Temple services that are usually provided for the public will also be dealt with. In the conclusion, an analysis of previous chapters will be given. An attempt to explain the importance of these public places of worship to the Chinese Community will also be included.